Analisis Six Sigma untuk Mengurangi Cacat Karton pada Mesin Wraparound - Eko, Syafrian; Sugiarto, Andriyas; Robiansyah, Mochamad Refly; Octavianto, Alvi; Kurnia, Hibarkah (Universitas Muhammadiyah Sorong, 2026)
This study aims to implement the Six Sigma method in the carton packaging production process using the Wraparound machine at PT. XYZ to enhance process capability and reduce defect levels. The research adopts the DMAIC (Define, Measure, Analyze, Improve, Control) approach. Initial measurements in the Measure stage were conducted using DPU, DPO, DPMO, and sigma level indicators, while the Control stage was used to evaluate the performance after improvements. Pareto analysis and fishbone diagrams were applied to identify dominant defects and their root causes. The findings show that open carton folds and misaligned carton folds were the dominant defects, with an initial sigma level of 3.97 and a DPMO of 6,784. After improvement actions such as machine setup standardization, preventive maintenance implementation, material quality enhancement, and operator training, the sigma level increased to 4.13 and the DPMO decreased to 4,281. The average defect rate also improved from 4.07% to 2.57%. These results indicate that the Six Sigma method is effective in improving quality, reducing defect rates, and optimizing the performance of the Wraparound machine at PT. XYZ.